Bladder cancer biomarkers: current approaches and future directions - Ahangar, Melika; Mahjoubi, Frouzandeh; Mowla, Seyed Javad (Frontiers in Oncology, 2024)
Bladder cancer is a significant health concern worldwide, necessitating effective diagnostic and monitoring strategies. Biomarkers play a crucial role in the early detection, prognosis, and treatment of this disease. This review explores the current landscape of bladder cancer biomarkers, including FDA-approved molecular biomarkers and emerging ones. FDA-approved molecular biomarkers, such as BTA stat, BTA TRAK, and NMP22, have been instrumental in diagnosing and monitoring bladder cancer. These biomarkers are derived from urinary samples and are particularly useful due to their sensitivity and specificity. As we move forward, we should continue to seek ways to optimize our processes and outcomes, these markers remain seriously challenged in the detection of early bladder cancer due to their limited sensitivity and specificity. For instance, sensitivities of BTA stat in bladder tumor detection have varied between 40-72%, while its specificities vary from 29-96%. In the same way, 70% sensitivity and 80% specificity have been recorded for BTA TRAK, while 11-85.7% sensitivity and 77-100% specificity have been documented for NMP22 BladderChek. The given variations, especially the low sensitivity in the diagnosis of bladder cancer at an early stage call for the invention of better diagnostic systems. Moreover, different sample collection and handling procedures applied in different laboratories further contribute to inconsistent results obtained. Extracellular vesicles (EVs) and exosomes, which carry a vast number of proteins, are being considered as potential biomarkers. Although these markers show promise, challenges remain due to non-standardized isolation techniques and lack of reproducibility across studies. Moreover, the discovery of new potential biomarkers is ongoing. For instance, the UBC® Rapid test and UBC ELISA kit, the XPERT BC Monitor, BC UroMark, TaqMan® Arrays, Soluble FAS (sFAS), Bladder tumor fibronectin (BTF), and IGF2 and MAGE-A3 are among the newest biomarkers under investigation. In conclusion, while bladder cancer biomarkers have shown great promise, more research is needed to standardize the testing procedures and validate these biomarkers in a clinical setting. This will pave the way for more accurate and efficient diagnosis and monitoring of bladder cancer, ultimately improving patient outcomes.